Malaysian employees perception pertaining to telework / Farzana Quoquab, Lim Chui Seong and Haider Ali Malik - Quoquab, Farzana; Lim, Chui Seong; Malik, Haider Ali (Faculty of Business Management, 2013)
The present research attempts to gain deeper understanding of Malaysian employees‟ perception pertaining to telework. Telephone and face-to-face interview generated 37 responses which revealed that mostly teleworking was viewed positively by the respondents. However, less team cohesiveness and socialization, lack of infrastructural support and direct supervision, and less control over the employees were mostly cited drawbacks in adopting telework. On the other hand, avoidance of traffic jam, reduced travelling time, saving cost, maintaining work and family life balance, increased productivity, trust, commitment and job satisfaction were mentioned as the benefits of telework. To avail these opportunities, it is indeed important for the Malaysian organizations to embrace this innovative work arrangement. However, the hindrance associated with telework is needed to be tackled with care. This study is among the pioneer in understanding the problems and prospects of telework adoption in Malaysia from a qualitative perspective which calls for more research to conduct in this field.